The Arts as a Venue for Developmental Science: Realizing a Latent Opportunity. Issue 5 (19th June 2017) - Goldstein, Thalia R.; Lerner, Matthew D.; Winner, Ellen
Abstract : Children in all cultures readily engage in artistic activities, yet the arts (dance, drama, drawing, and music) have traditionally been marginal topics in the discipline of developmental science. We argue that developmental psychologists cannot afford to ignore such naturalistic activities that involve so many basic phenomena—attention, engagement, motivation, emotion regulation, understanding of others, and so on. Despite historical issues with research methodologies and overdrawn conclusions, a current wave of methodologically rigorous studies shows the depth of arts learning, as well as how arts engagement can be harnessed for transfer to other skills. Here, we present 21 exemplary research case studies, covering an age range of 18 months to 17 years old and discuss how the arts are no more difficult to study than other real‐world developmental phenomena and deserve a thorough examination. Abstract : The title for this Special Section isBringing Developmental Science into the World, edited by Roberta Michnick Golinkoff, Kathy Hirsh‐Pasek, Rachel Grob, and Mark Schlesinger